2021
DOI: 10.3390/medicina57020121
|View full text |Cite
|
Sign up to set email alerts
|

Acute Clinical Syndromes and Suspicion of SARS-CoV-2 Infection: The Experience of a Single Romanian Center in the Early Pandemic Period

Abstract: Background and Objectives: During the coronavirus disease 2019 (COVID-19) pandemic, patients with chronic diseases suffering exacerbations have required acute medical care. The purpose of our study was to determine useful criteria for the differentiation of patients with acute clinical syndromes and suspicion of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Materials and Methods: This was an observational retrospective study, conducted in an internal medicine clinic from April to May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Low levels of iron have been reported in Romanian patients early on, accordingly to international data [ 56 , 72 , 88 ]; however, there have been cases of normal values reported [ 54 , 86 , 89 , 90 ], while others have reported high levels of FER, including in children [ 14 , 21 , 23 , 24 , 25 , 26 , 29 , 30 , 31 , 35 , 36 , 41 , 43 , 48 , 62 , 74 , 79 ], with a few rare cases of vertical transmission describing increased FER levels, as observed in Iacob et al’s study [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of iron have been reported in Romanian patients early on, accordingly to international data [ 56 , 72 , 88 ]; however, there have been cases of normal values reported [ 54 , 86 , 89 , 90 ], while others have reported high levels of FER, including in children [ 14 , 21 , 23 , 24 , 25 , 26 , 29 , 30 , 31 , 35 , 36 , 41 , 43 , 48 , 62 , 74 , 79 ], with a few rare cases of vertical transmission describing increased FER levels, as observed in Iacob et al’s study [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Normal cardiac markers were observed in a few studies [ 21 , 86 ], while elevated levels were observed in others [ 23 , 37 , 45 , 63 , 74 ]. Furthermore, cardiac markers varied by NYHA classification and were considered an independent risk factor [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…This infectious disease has a wild range of clinical symptoms, starting from mild respiratory illness with fever, cough, myalgia, headache, anosmia and diarrhea to severe pneumonia with acute respiratory distress syndrome, cardiac arrhythmias, septic shock, hypercoagulability, disseminated intra-vascular coagulation with multi-organ failure and even death [ 12 ]. These clinical features help in identifying the patients suffering from SARS-CoV-2 infection even before the RT-PCR for COVID-19 comes back as positive; therefore, they help in managing these patients in a timely manner [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main cause of death in COVID-19 patients is documented as acute respiratory distress. The cardiovascular system and shock are also often implicated [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%